Longterm and Peakscan : neutron activation analysis computer programs - Meyers, Thomas; Denies, Mark (Technical reports (University of Michigan. Museum of Anthropology), 1972)
In this work, the authors present the history of efforts at the University of Michigan to develop specialized laboratory techniques suitable for measuring trace elements found in prehistoric artifacts. They explain how two early computer programs (PEAKSCAN and LONGTERM) analyzed specimens (particularly chert and obsidian) and how neutron activation analysis is used to identify quantities of certain chemical elements. Researchers then use this data to determine the sources of raw materials used by prehistoric people.